Acromegaly incidence, prevalence, complications and long-term prognosis: a nationwide cohort study. Issue 3 (September 2016) - Dal, Jakob; Feldt-Rasmussen, Ulla; Andersen, Marianne; Kristensen, Lars Ø; Laurberg, Peter; Pedersen, Lars; Dekkers, Olaf M; Sørensen, Henrik Toft; Jørgensen, Jens Otto L
Abstract : Design: Valid data on acromegaly incidence, complications and mortality are scarce. The Danish Health Care System enables nationwide studies with complete follow-up and linkage among health-related databases to assess acromegaly incidence, prevalence, complications and mortality in a population-based cohort study. Method: All incident cases of acromegaly in Denmark (1991–2010) were identified from health registries and validated by chart review. We estimated the annual incidence rate of acromegaly per 10 6 person-years (py) with 95% confidence intervals (95% CIs). For every patient, 10 persons were sampled from the general population as a comparison cohort. Cox regression and hazard ratios (HRs) with 95% confidence intervals (95% CIs) were used. Results: Mean age at diagnosis (48.7 years (CI: 95%: 47.2–50.1)) and annual incidence rate (3.8 cases/10 6 persons (95% CI: 3.6–4.1)) among the 405 cases remained stable. The prevalence in 2010 was 85 cases/10 6 persons. The patients were at increased risk of diabetes mellitus (HR: 4.0 (95% CI: 2.7–5.8)), heart failure (HR: 2.5 (95% CI: 1.4–4.5)), venous thromboembolism (HR: 2.3 (95% CI: 1.1–5.0)), sleep apnoea (HR: 11.7 (95% CI: 7.0–19.4)) and arthropathy (HR: 2.1 (95% CI: 1.6–2.6)). The complication risk was also increased before the diagnosis of acromegaly. Overall mortality risk was elevated (HR: 1.3 (95% CI: 1.0–1.7)) but uninfluenced by treatment modality. Conclusion: (i) The incidence rate and age at diagnosis of acromegaly have been stable over decades, and the prevalence is higher than previously reported. (ii) The risk of complications is very high even before the diagnosis. (iii) Mortality risk remains elevated but uninfluenced by mode of treatment.